2021
DOI: 10.3390/su13052974
|View full text |Cite
|
Sign up to set email alerts
|

Excavation Method Determination of Earth-Retaining Wall for Sustainable Environment and Economy: Life Cycle Assessment Based on Construction Cases in Korea

Abstract: This study describes life cycle assessment (LCA) results of the excavation depth and ground condition of a medium-sized excavation ground in order to examine the effect of construction methods on environmental and economic feasibility for an earth-retaining wall. LCA is conducted in consideration of eight environmental impact categories according to the construction stage of the earth-retaining wall. In addition, the environmental cost of construction method for the earth-retaining wall was calculated, and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Some studies analyzed the effects of data quality (Inui et (Lee and Basu 2016, Purdy et al 2022, Speranza et al 2022. Though not a sensitivity study, Seol et al (2021) embedded varying soil conditions and properties in their study. Sánchez-Garrido et al (2022) validated results by implementing different multi-criteria decision-making procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies analyzed the effects of data quality (Inui et (Lee and Basu 2016, Purdy et al 2022, Speranza et al 2022. Though not a sensitivity study, Seol et al (2021) embedded varying soil conditions and properties in their study. Sánchez-Garrido et al (2022) validated results by implementing different multi-criteria decision-making procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Leal et al (2020) reported that material haulage accounted for more than 50% of GWP. Seol et al (2021) also applied the environmental costs per unit of pollutants for each reported impact categories.…”
Section: Earth Retaining Structuresmentioning
confidence: 99%
“…From the design perspective, these discussions are relevant if knowledge about the environmental performance of different, equally feasible solutions would change the decision about which type of, for example, foundation or stability measure will be used in a specific situation. Seol et al [10] used LCAs to compare different construction methods for urban excavations in Korea. They concluded that consideration of the environmental impact in design would influence the choice of method.…”
Section: Introductionmentioning
confidence: 99%
“…A popular foundation variant was selected as a good example of the potential application of this design method (i.e., construction of high-rise buildings in a dense urban development [18,19]): the execution of four or more underground floors in the sheathing of diaphragm walls using the ceiling or Top-down method. Section 1 describes some historical data on prestressing concrete, and a scientific connection between prestressing and diaphragm walls; Section 2 presents an analytical method of designing prestressed structures; Section 3 is related to bridge and geotechnical solutions in the Sofistik environment; Section 4 shows comparison of the suggested solution models prepared with the Sofistik and Plaxis software; Section 5 presents conclusions.…”
Section: Introductionmentioning
confidence: 99%